Strength properties of ultra-soft kaolin - Sahdi, F.; Gaudin, C.; White, D.J. (Canadian Geotechnical Journal, 2013)
Geotechnical design considerations for offshore pipelines, foundations, and submarine slides involve assessment of the strength of fine-grained soils and the degradation of that strength with disturbance and remoulding. For offshore pipelines and slides, the relevant strength may be very low (a few kilopascals or lower), relating to near-surface soils and high levels of remoulding including the entrainment of additional water. It is commonly acknowledged that soils exhibit a loss of strength when disturbed, but it is not clear how the degradation properties vary with liquidity index. To address this uncertainty, this paper describes a series of centrifuge tests on kaolin samples consolidated from slurries with an initial voids ratio of 4.0. A total of 81 cyclic T-bar tests were conducted in samples with shear strengths ranging from 0.08 to 1.7 kPa (reflecting different stages of consolidation and in situ total stresses). Large-strain consolidation numerical analyses were used to assist the interpretation of the T-bar test results. The results demonstrate that the soil ductility (a parameter controlling the rate of strength degradation) can be linearly correlated to the liquidity index. The proposed ductility–liquidity index correlation is subsequently coupled with a previously published sensitivity–liquidity index relationship for natural clays to establish a model for the strain-softening behaviour observed in a T-bar test as a function of consolidation. In turn, because the sensitivity is a function of the liquidity index, the intact soil strength is linked to the remoulded strength obtained from laboratory (e.g., fall cone or miniature vane test) and simple index tests. These provide an improved basis to characterize softening effects for inclusion in simulations of submarine slide runout and models for soil–structure interactions that involve intense remoulding.